PENDIDIKAN KELUARGA DALAM PEMBENTUKAN KARAKTER MANDIRI DI PANTI ASUHAN AN-NURIYYAH - Untoro, Hanifah Salwa; Suminar, Uum; Pujiarto, Pujiarto (IKIP Siliwangi, 2025)
Family Education in Developing Independent Character at An-Nuriyyah Orphanage. Faculty of Teacher Training and Education, Singaperbangsa University, Karawang. This study aims to determine how the implementation of family education in social institutions, particularly orphanages, shapes the independent character of children in orphanages. Children living in orphanages generally come from broken or less harmonious family backgrounds, thus lacking direct family education experience from their biological parents. Therefore, the role of caregivers is crucial as substitutes for families, not only responsible for caring for and protecting but also guiding and educating children in their daily lives. Family education in this context is aimed at fostering independent character, namely the child's ability to solve problems, make decisions, act consistently, and not depend on others. This study used a qualitative approach with data collection techniques through observation, interviews, and documentation.